Passive transfer of antiviral antibodies restricts replication of Aleutian mink disease parvovirus in vivo. - Alexandersen, S (1989)
When mink kits were infected neonatally with a highly virulent strain of Aleutian disease virus (ADV), 100% of both Aleutian and non-Aleutian genotype mink died of interstitial pneumonia characterized by permissive ADV infection of alveolar type II cells. Treatment of infected kits with either mink anti-ADV gamma globulin or mouse monoclonal antibodies against ADV structural proteins reduced mortality by 50 to 75% and drastically reduced the severity of clinical signs. Interestingly, mink kits that survived the acute pulmonary disease all developed the chronic form of immune complex-mediated Aleutian disease. Thus, the antibodies directed against ADV structural proteins were capable of modulating the in vivo pathogenicity from an acute fulminant disease to a chronic immune complex-mediated disorder. The mechanism of this modulation was examined by strand-specific in situ hybridization. We found that the number of ADV-infected type II cells was the same in both untreated and antibody-treated kits. However, in the treated kits, viral replication and transcription were restricted at the cellular level. These data suggested that antibodies prevented acute viral pneumonia by restricting the intracellular level of viral replication and that the relevant antigenic determinants were contained within the viral structural proteins. The restricted levels of viral replication and transcription seen in antibody-treated mink kits resembled the levels observed in infected adult mink and suggested a role of antiviral antibodies in development of persistent infection and chronic immune complex disease.